Thickness-modulated tungsten–carbon superconducting nanostructures grown by focused ion beam induced deposition for vortex pinning up to high magnetic fields - Serrano, Ismael García; Sesé, Javier; Guillamón, Isabel; Suderow, Hermann; Vieira, Sebastián; Ibarra, Manuel Ricardo; De Teresa, José María (Beilstein Journal of Nanotechnology, 2016)
We report efficient vortex pinning in thickness-modulated tungsten–carbon-based (W–C) nanostructures grown by focused ion beam induced deposition (FIBID). By using FIBID, W–C superconducting films have been created with thickness modulation properties exhibiting periodicity from 60 to 140 nm, leading to a strong pinning potential for the vortex lattice. This produces local minima in the resistivity up to high magnetic fields (2.2 T) in a broad temperature range due to commensurability effects between the pinning potential and the vortex lattice. The results show that the combination of single-step FIBID fabrication of superconducting nanostructures with built-in artificial pinning landscapes and the small intrinsic random pinning potential of this material produces strong periodic pinning potentials, maximizing the opportunities for the investigation of fundamental aspects in vortex science under changing external stimuli (e.g., temperature, magnetic field, electrical current).
Keywords: focused ion beam induced deposition; magnetotransport; superconductivity; vortex lattice

(untitled) - van Dorp, W. F.; Hagen, C. W. (J. Appl. Phys., 2008)

(untitled) - Utke, I.; Hoffmann, P.; Melngailis, J. (J. Vac. Sci. Technol., B, 2008)

(untitled) - Randolph, S. J.; Fowlkes, J. D.; Rack, P. D. (Crit. Rev. Solid State Mater. Sci., 2006)

(untitled) - De Teresa, J. M.; Fernández-Pacheco, A.; Córdoba, R.; Serrano-Ramón, L.; Sangiao, S.; Ibarra, M. R. (J. Phys. D, 2016)

(untitled) - Huth, M.; Porrati, F.; Schwalb, C.; Winhold, M.; Sachser, R.; Dukic, M.; Adams, J.; Fantner, G. (Beilstein J. Nanotechnol., 2012)

(untitled) - Riazanova, A. V.; Costanzi, B. N.; Aristov, A.; Rikers, Y. G. M.; Ström, V.; Mulders, J. J. L.; Kabashin, A. V.; Dahlberg, E. D.; Belova, L. M. (Nanotechnology, 2014)

(untitled) - Utke, I.; Hoffmann, P.; Berger, R.; Scandella, L. (Appl. Phys. Lett., 2002)

(untitled) - Graells, S.; Aćimović, S.; Volpe, G.; Quidant, R. (Plasmonics, 2010)

(untitled) - Sadki, E. S.; Ooi, S.; Hirata, K. (Appl. Phys. Lett., 2004)

(untitled) - Kasumov, A. Yu.; Tsukagoshi, K.; Kawamura, M.; Kobayashi, T.; Aoyagi, Y.; Senba, K.; Kodama, T.; Nishikawa, H.; Ikemoto, I.; Kikuchi, K.; Volkov, V. T.; Kasumov, Yu. A.; et al. (Phys. Rev. B, 2005)

(untitled) - Luxmoore, I. J.; Ross, I. M.; Cullis, A. G.; Fry, P. W.; Orr, J.; Buckle, P. D.; Jefferson, J. H. (Thin Solid Films, 2007)

(untitled) - Spoddig, D.; Schindler, K.; Rödiger, P.; Barzola-Quiquia, J.; Fritsch, K.; Mulders, H.; Esquinazi, P. (Nanotechnology, 2007)

(untitled) - Guillamón, I.; Suderow, H.; Vieira, S.; Fernández-Pacheco, A.; Sesé, J.; Córdoba, R.; De Teresa, J. M.; Ibarra, M. R. (New J. Phys., 2008)

(untitled) - Li, W.; Fenton, J. C.; Warburton, P. A. (IEEE Trans. Appl. Supercond., 2009)

(untitled) - Guillamón, I.; Suderow, H.; Fernández-Pacheco, A.; Sesé, J.; Córdoba, R.; De Teresa, J. M.; Ibarra, M. R.; Vieira, S. (Nat. Phys., 2009)

(untitled) - Wang, J.; Shi, C.; Tian, M.; Zhang, Q.; Kumar, N.; Jain, J. K.; Mallouk, T. E.; Chan, M. H. W. (Phys. Rev. Lett., 2009)

(untitled) - Córdoba, R.; Baturina, T. I.; Sesé, J.; Mironov, A. Y.; De Teresa, J. M.; Ibarra, M. R.; Nasimov, D. A.; Gutakovskii, A. K.; Latyshev, A. V.; Guillamón, I.; Suderow, H.; Vieira, S.; et al. (Nat. Commun., 2013)

(untitled) - Sun, Y.; Wang, J.; Zhao, W.; Tian, M.; Singh, M.; Chan, M. H. W. (Sci. Rep., 2013)

(untitled) - Dai, J.; Kometani, R.; Onomitsu, K.; Krockenberger, Y.; Yamaguchi, H.; Ishihara, S.; Warisawa, S. (J. Micromech. Microeng., 2014)

(untitled) - Guillamón, I.; Suderow, H.; Vieira, S.; Sesé, J.; Córdoba, R.; De Teresa, J. M.; Ibarra, M. R. (Phys. Rev. Lett., 2011)

(untitled) - Guillamón, I.; Córdoba, R.; Sesé, J.; De Teresa, J. M.; Ibarra, M. R.; Vieira, S.; Suderow, H. (Nat. Phys., 2014)

(untitled) - De Teresa, J. M.; Córdoba, R. (ACS Nano, 2014)

(untitled) - Abrikosov, A. A. (Sov. Phys. - JETP, 1957)

(untitled) - Blatter, G.; Feigel'man, F. V.; Geshkenbein, V. B.; Larkin, A. I.; Vinokur, V. M. (Rev. Mod. Phys., 1994)

(untitled) - Morrison, D. D.; Rose, R. M. (Phys. Rev. Lett., 1970)

(untitled) - Raffy, H.; Renard, J. C.; Guyon, E. (Solid State Commun., 1972)

(untitled) - Daldini, O.; Martinoli, P.; Olsen, J. L.; Berner, G. (Phys. Rev. Lett., 1974)

(untitled) - Martinoli, P. (Phys. Rev. B, 1978)

(untitled) - Civale, L.; Marwick, A. D.; Worthington, T. K.; Kirk, M. A.; Thompson, J. R.; Krusin-Elbaum, L.; Sun, Y.; Clem, J. R.; Holtzberg, F. (Phys. Rev. Lett., 1991)

(untitled) - Jaque, D.; González, E. M.; Martin, J. I.; Anguita, J. V.; Vicent, J. L. (Appl. Phys. Lett., 2002)

(untitled) - Plourde, B. L. T.; Van Harlingen, D. J.; Saha, N.; Besseling, R.; Hesselberth, M. B. S.; Kes, P. H. (Phys. Rev. B, 2002)

(untitled) - Lange, M.; Van Bael, M. J.; Bruynseraede, Y.; Moshchalkov, V. V. (Phys. Rev. Lett., 2003)

(untitled) - Raedts, S.; Silhanek, A. V.; Van Bael, M. J.; Moshchalkov, V. V. (Phys. Rev. B, 2004)

(untitled) - Villegas, J. E.; Gonzalez, E. M.; Gonzalez, M. P.; Anguita, J. V.; Vicent, J. L. (Phys. Rev. B, 2005)

(untitled) - Gutiérrez, J.; Llordés, A.; Gázquez, J.; Gibert, M.; Romà, N.; Ricart, S.; Pomar, A.; Sandiumenge, F.; Mestres, N.; Puig, T.; Obradors, X. (Nat. Mater., 2007)

(untitled) - Vélez, M.; Martín, J. I.; Villegas, J. E.; Hoffmann, A.; González, E. M. M.; Vicent, J. L. L.; Schuller, I. K. (J. Magn. Magn. Mater., 2008)

(untitled) - Llordés, A.; Palau, A.; Gázquez, J.; Coll, M.; Vlad, R.; Pomar, A.; Arbiol, J.; Guzmán, R.; Ye, S.; Rouco, V.; Sandiumenge, F.; Ricart, S.; et al. (Nat. Mater., 2012)

(untitled) - Swiecicki, I.; Ulysse, C.; Wolf, T.; Bernard, R.; Bergeal, N.; Briatico, J.; Faini, G.; Lesueur, J.; Villegas, J. E. (Phys. Rev. B, 2012)

(untitled) - Wang, Y. L.; Latimer, M. L.; Xiao, Z. L.; Divan, R.; Ocola, L. E.; Crabtree, G. W.; Kwok, W. K. (Phys. Rev. B, 2013)

(untitled) - Palau, A.; Rouco, V.; Luccas, R. F.; Obradors, X.; Puig, T. (Physica C, 2014)

(untitled) - Trastoy, J.; Malnou, M.; Ulysse, C.; Bernard, R.; Bergeal, N.; Faini, G.; Lesueur, J.; Briatico, J.; Villegas, J. E. (Nat. Nanotechnol., 2014)

(untitled) - Dobrovolskiy, O. V.; Huth, M. (Appl. Phys. Lett., 2015)

(untitled) - Surdu, A. E.; Hamdeh, H. H.; Al-Omari, I. A.; Sellmyer, D. J.; Socrovisciuc, A. V.; Prepelita, A. A.; Koparan, E. T.; Yanmaz, E.; Ryazanov, V. V.; Hahn, H.; Sidorenko, A. S. (Beilstein J. Nanotechnol., 2011)

(untitled) - Sidorenko, A.; Zdravkov, V.; Ryazanov, V.; Horn, S.; Klimm, S.; Tidecks, R.; Wixforth, A.; Koch, T.; Schimmel, T. (Philos. Mag., 2005)

Studies of High Temperature Superconductors - Eisenmenger, J.; Ziemann, P. (Effect of Dimensional Restrictions on the Vortex Dynamics in Tl2Ba2CaCu2O8 thin Films, 2005)

(untitled) - Dobrovolskiy, O. V. (Physica C, 2016)

(untitled) - Pautrat, A.; Scola, J.; Goupil, C.; Simon, C.; Villard, C.; Domengès, B.; Simon, Y.; Guilpin, C.; Méchin, L. (Phys. Rev. B, 2004)

(untitled) - Dobrovolskiy, O. V.; Begun, E.; Huth, M.; Shklovskij, V. A. (New J. Phys., 2012)

Functional Nanostructures Fabricated by Focused Electron/Ion Beam Induced Deposition - Córdoba, R. (Springer, 2014)

(untitled) - Guillamón, I.; Suderow, H.; Vieira, S.; Fernández-Pacheco, A.; Sesé, J.; Córdoba, R.; De Teresa, J. M.; Ibarra, M. R. (J. Phys.: Conf. Ser., 2009)

(untitled) - Gomez, A.; del Valle, J.; Gonzalez, E. M.; Chiliotte, C. E.; Carreira, S. J.; Bekeris, V.; Prieto, J. L.; Schuller, I. K.; Vicent, J. L. (Supercond. Sci. Technol., 2014)

(untitled) - Le Thien, Q.; McDermott, D.; Olson Reichhardt, C. J.; Reichhardt, C. (Phys. Rev. B, 2016)

(untitled) - Poccia, N.; Baturina, T. I.; Coneri, F.; Molenaar, C. G.; Wang, X. R.; Bianconi, G.; Brinkman, A.; Hilgenkamp, H.; Golubov, A. A.; Vinokur, V. M. (Science, 2015)

(untitled) - Martínez-Pérez, M. J.; Sesé, J.; Córdoba, R.; Luis, F.; Drung, D.; Schurig, T. (Supercond. Sci. Technol., 2009)